2023
DOI: 10.1186/s12859-023-05425-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular complex detection in protein interaction networks through reinforcement learning

Abstract: Background Proteins often assemble into higher-order complexes to perform their biological functions. Such protein–protein interactions (PPI) are often experimentally measured for pairs of proteins and summarized in a weighted PPI network, to which community detection algorithms can be applied to define the various higher-order protein complexes. Current methods include unsupervised and supervised approaches, often assuming that protein complexes manifest only as dense subgraphs. Utilizing supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Unfortunately, the prediction performance provided by the above approaches appears to be unsatisfactory. Recently, reinforcement learning (RL) was used to detect new molecular complexes in PPI networks 24,25 . The results from Palukuri, et al showed that RL algorithm had good performance on the human PPI dataset 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the prediction performance provided by the above approaches appears to be unsatisfactory. Recently, reinforcement learning (RL) was used to detect new molecular complexes in PPI networks 24,25 . The results from Palukuri, et al showed that RL algorithm had good performance on the human PPI dataset 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, reinforcement learning (RL) was used to detect new molecular complexes in PPI networks 24,25 . The results from Palukuri, et al showed that RL algorithm had good performance on the human PPI dataset 24 . However, it is unclear whether it can be used in other scenarios.…”
Section: Introductionmentioning
confidence: 99%